Designing a cyber-physical robotic platform to assist speech-language pathologists. - Caldwell Marin, Eldon Glen; Morales, Carlos Andres; Solis Sanchez, Emilia; Cazorla, Miguel; Cañas Plaza, Jose Maria (Assistive Technology, 2023)
This research focused on the development of a cyber-physical robotic platform to assist speech-language pathologists who are related to articulation disorders in education environments. The first goal was the design and development of the system. The second goal was the qualitative initial validation of the platform with robotics and mobile device functionalities drawing on the participation of real patients and speech-language pathologists (SLP). The research method is based on qualitative data. The first phase was the application of engineering requirements and agile techniques to build the robotic system. The second phase was to execute test sessions of the robotic platform with speech-language pathologists supervision and analyzing the experience of real male and female patients collecting data by in-depth interviews and video recordings at Heredia Special Education Center in Costa Rica. The practical approach of the cyber-physical platform has preliminarily support. Testing with SLPs and 3 other older individuals suggests that it may become a useful tool to assist professionals in the treatment of some types of articulation disorders. The time savings and data collection possibilities should be included in future investigations of efficacy.